Poverty and mass education: The Jews in the Roman empire - David Aberbach (London School of Economics and Political Science (LSE), Department of International Development, 2018)
Since 1789, mass education has been a key factor in development, enablinglarge numbers of people to escape at least the worst effects of poverty. This paper explores an ancient harbinger of mass education, among Jews in the Roman empire, the basis of Jewish religious education to modern times. Education became vital to Jewish survival after three disastrous wars against Rome (66-73, 115-117, and 132-135 CE), when the Jewish state was destroyed together with Jerusalem and its Temple, the centre of Jewish religion, as well as the Temple priesthood and Jewish aristocracy, leaving the authority of the Torah to its teachers. The sacred culture of education came to dominate the lives of most European Jews until 1789 and was instrumental in their ability to make use of educational systems created by newly emerging secular states, mostly in Western Europe after 1789 and in America after 1881, and in their consequent economic improvement.
Keywords: 330; history of development; poverty and education; nationalism; Roman-Jewish history; Hebrew literature; modern Jewish social studies